A multifunctional AIEgen with high cell-penetrating ability for intracellular fluorescence assays, imaging and drug delivery. (24th April 2019) - Li, Yan Jie; Zhang, Hao Tian; Chen, Xiao Ying; Gao, Peng Fei; Hu, Chang-Hua
Abstract : A diethylamino-modified multifunctional ESIPT AIEgen with superior cell-penetrating capacity is applied for intracellular fluorescence assays, imaging and drug delivery. Abstract : Aggregation-induced emission luminogens (AIEgens) with a definite structure–activity relationship play important roles in site-specific bio-imaging and applications. However, the lack of a clear structure–activity relationship for the excited-state intramolecular proton transfer (ESIPT) molecules, which are a series of powerful AIEgens, restricts their biological applications. Herein, the cell-penetrating capability of 4- N, N -dimethylaminoaniline salicylaldehyde Schiff-bases (DSS) with different substituents was investigated. The diethylamino functionalized ESIPT Schiff base (DSS-4-DEA) displayed high cell-penetrating capacity, making this simple AIEgen turn into a more powerful fluorescent functional material in biosystems. The DSS-4-DEA was successfully used for a fluorescence assay of the intracellular Cu 2+ . Besides, the DSS-4-DEA could also be used as an efficient transmembrane carrier to drastically enhance the internalization of DSS-5-Cl to achieve two-color imaging. In addition, the DSS-4-DEA could be used to improve the transportation of anticancer drug curcumin (Cur) into HeLa cells, leading to increased apoptosis. The complete exploration of the structure–activity relationship of ESIPT molecules might supply lots of new applications of AIE materials in biological systems.